Observed infant-parent attachment and brain morphology in middle childhood– A population-based study. (December 2019) - Cortes Hidalgo, Andrea P.; Muetzel, Ryan; Luijk, Maartje P.C.M.; Bakermans-Kranenburg, Marian J.; El Marroun, Hanan; Vernooij, Meike W.; van IJzendoorn, Marinus H.; White, Tonya; Tiemeier, Henning
Abstract: Poor quality of the early infant-parent bond predicts later child problems. Infant-parent attachment has been suggested to influence brain development, but this association has hardly been examined. In adults, larger amygdala volumes have been described in relation to early attachment disorganization; neuroimaging studies of attachment in children, however, are lacking. We examined the association between infant-parent attachment and brain morphology in 551 children from a population-based cohort in the Netherlands. Infant-parent attachment was observed with the Strange-Situation Procedure at age 14 months and different brain measures were collected with magnetic resonance imaging at mean age 10 years. Children with disorganized infant attachment had larger hippocampal volumes than those with organized attachment patterns. This finding was robust to the adjustment for confounders and consistent across hemispheres. The association was not explained by cognitive or emotional and behavioral problems. Disorganized attachment did not predict any other difference in brain morphology. Moreover, children with insecure organized infant attachment patterns did not differ from those who were securely attached in any brain outcome. Causality cannot be inferred, but our findings in this large population-based study provide novel evidence for a long-term association between the quality of infant-parent attachment and specific brain differences in childhood.